Strategi Komunikasi dalam Mensosialisasikan Program Website Layanan Aspirasi dan Pengaduan Online Rakyat - Elpiana Rossa; Muhammad Alfikri (SOCIETAS, 2023)
This study aims to analyze the communication strategy used in socializing the Online People's Aspirations and Complaint Service (LAPOR) website program in Pematang Siantar City, North Sumatra. This study uses a qualitative approach with data collection techniques in the form of interviews, literature studies and observations. The results showed that there were five communication strategies used in socializing the LAPOR program Utilizing social media, Holding exhibitions about the People's Online Aspirations and Complaint Service Program (LAPOR), Providing training on how to use the Lapor program, Placing Banners and Banners about the Report program, and Conducting roadshows to various areas in Pematang Siantar City. Active government involvement and community participation is critical to the success of the Lapor program. The government's active involvement can increase public trust and motivate them to use the Lapor program. Through the use of the right strategy, it is hoped that the Lapor program can continue to grow and provide benefits to the community.